Viral Encephalitis and Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs)
The role of viral meningitis in the cause of epilepsy is reviewed by researchers from Sanjay Gandhi Postgraduate Institute of Medical Sciences, Lucknow, India; and University of Malaya, Kuala Lumpur, Malaysia.